Conventional Therapy and Promising Plant-Derived Compounds Against Trypanosomatid Parasites - Alviano, Daniela S.; Barreto, Anna Léa S.; Dias, Felipe d.; Rodrigues, Igor d.; Rosa, Maria do Socorro dos Santos Rosa; Alviano, Celuta S.; Soares, Rosangela Maria d. (Frontiers in Microbiology, 2012)
Leishmaniasis and trypanosomiasis are two neglected and potentially lethal diseases that affect mostly the poor and marginal populations of developing countries around the world and consequently have an important impact on public health. Clinical manifestations such as cutaneous, mucocutaneous and visceral disorders are the most frequent forms of leishmaniasis, a group of diseases caused by several Leishmania spp. American trypanosomiasis, or Chagas disease, is caused by Trypanosoma cruzi, a parasite that causes progressive damage to different organs, particularly the heart, esophagus and lower intestine. African trypanosomiasis, or sleeping sickness, is caused by Trypanosoma brucei and is characterized by first presenting as an acute form that affects blood clotting and then becoming a chronic meningoencephalitis. The limited number, low efficacy and side effects of conventional anti-leishmania and anti-trypanosomal drugs and the resistance developed by parasites are the major factors responsible for the growth in mortality rates. Recent research focused on plants has shown an ingenious way to obtain a solid and potentially rich source of drug candidates against various infectious diseases. Bioactive phytocompounds present in the crude extracts and essential oils of medicinal plants are components of an important strategy linked to the discovery of new medicines. These compounds have proven to be a good source of therapeutic agents for the treatment of leishmaniasis and trypanosomiasis. This work highlights some chemotherapeutic agents while emphasizing the importance of plants as a source of new and powerful drugs against these widespread diseases.